Description of Risk Factors for Anemia in Pregnant Women in Jorong Kajai Koto Baru (HEALTH CARE: JURNAL KESEHATAN, 2025)
Introduction: Anemia during pregnancy is one of the main health problems in mothers and children and there are still many pregnant women who experience anemia in Jorong Kajai Koto Baru. In Solok Regency, in 2022, examining the causes of maternal death. Starting from pregnancy, management of childbirth and postpartum period and chronology of cases until death in a comprehensive manner, namely: bio, psychological, social and spiritual. From the results of the audit, the causes of maternal death include: Eclampsia, Severe Preeclampsia, Anemia of Pregnant Women, Pregnant Women's age 50 years with ≥ 3 children. Objective: To see an overview of the risk factors for anemia in pregnant women Method: The type of research used is descriptive with a cross-sectional approach. The population in this study were pregnant women who experienced anemia with a total sampling technique of 36 people.Results: The results of the study showed that possible risk factors for anemia were pregnant women aged 20-35 years, high education level, parity level at risk of ³ 4 times, and mothers who did not work Conclusion: Possible risk factors for anemia are pregnant women aged 20-35 years, high education levels, high-risk parity levels, and not working in Jorong Kajai Koto Baru Solok in 2024.